PENINGKATAN KOMPETENSI GURU DALAM PENYUSUNAN RPP DENGAN MENERAPKAN MODEL-MODEL PEMBELAJARAN MELALUI TEKNIK COACHING - Padmi Andarini; Rahmat Mulyono (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2022)
The background of this research is due to the low ability of SDN Gotakan teachers to arrange lesson plans. The lesson plans that have been prepared have not utilized the 21st century learning model and have not actively engaged students in learning activities. This study aims to improve teacher competence in preparing lesson plans by applying learning models and describing coaching steps that can improve teacher competence in preparing lesson plans by utilizing learning models. This study employs the Kemmis and McTaggart model of school action research. This study's research procedure includes planning, action, observation, and reflection. This study was divided into two cycles of four meetings each. The research subjects consisted of six classroom teachers. This school action research was conducted in a collaborative and participatory manner. Research data were taken using observation sheets. These activities include the following: the implementation of coaching with technical coaching, the results of the guidance in the form of lesson plans, and the implementation of teacher presentations. The results of the preparation of the lesson plans in the first cycle—the characteristics of the material, learning objectives, and learning steps were not in accordance with the selected learning model. In the second cycle, the principal provided mentoring once more. The results of the second cycle's lesson plan preparation—the characteristics of the material, learning objectives, and learning steps—were coherent with the chosen learning model. In conclusion, through the guidance of the couching model, it is possible to improve teacher competence in preparing lesson plans by applying learning models at SD Negeri Gotakan in 2022.